Understanding quality assurance in construction : a practical guide to ISO 9000 for contractors - Chung, H. W. (Hung W.) (E & FN Spon, 1999)
This is a practical guide for building and construction contractors and sub-contractors and other construction professionals. Also for undergraduate and postgraduate students of building and construction.